ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PELAKU UMKM DI KELURAHAN TAMALATE KECAMATAN KOTA TIMUR KOTA GORONTALO - Malango, Zulyana; Imbran, Harijono H; Machmud, Joice (Universitas Muhammadiyah Gorontalo, 2025)
This study aims to identify internal and external factors that influencing the income of SME operators in Tamalate Village, Kota Timur District, Gorontalo City. The instruments used in this research were interviews and questionnaires with a Likert scale approach, supported by regression and multiple correlation analysis. The respondents in this study consisted of 40 MSME respondents. The results of the analysis showed that internal factors (efficiency, competitiveness of product quality including packaging) and external factors (capital, access to business financing, and competitiveness) simultaneously have a strong (significant) influence, with an R-Square value of 0.781 or 78.1 percent.